2019
DOI: 10.1002/cbf.3462
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐associated fibroblasts–derived exosomes‐mediated transfer of LINC00355 regulates bladder cancer cell proliferation and invasion

Abstract: The aim of this study was to investigate the regulatory mechanism of cancerassociated fibroblasts (CAFs) exosome in bladder cancer (BC) cell proliferation and invasion. CAFs and normal fibroblasts (NFs) were isolated from tumor tissues and adjacent normal tissues of BC patients, and examined by immunocytochemistry for the expression of fibroblast activation protein alpha (FAP) and α-smooth muscle actin (α-SMA). Exosomes were extracted from CAFs and NFs and observed under a transmission electron microscope, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…Our data are consistent with the newly recent reports about LINC00355 acting as an oncogene in other cancers, including bladder cancer, head and neck squamous cell carcinoma, and lung adenocarcinoma [43][44][45] .…”
Section: Discussionsupporting
confidence: 93%
“…Our data are consistent with the newly recent reports about LINC00355 acting as an oncogene in other cancers, including bladder cancer, head and neck squamous cell carcinoma, and lung adenocarcinoma [43][44][45] .…”
Section: Discussionsupporting
confidence: 93%
“…We found that the CDC25C/CDK1/RRM2-LINC00355 ceRNA relationship can affect non-small cell lung cancer. It is reported in recent studies that exosomes-mediated LINC00355 regulates bladder cancer cell proliferation and invasion [ 38 ]. Identification of these markers will further improve understanding of lncRNA-mediated pathway regulation and ceRNA functions.…”
Section: Discussionmentioning
confidence: 99%
“…A study of exosomes secreted from cancer cells showed stimulation of fibroblasts into myofibroblast through tumor growth factor (TGF)-β , thereby contributing to tumor progression 28 . In another study, the increase in LINC00355 expression of CAFs promoted the proliferation and invasiveness of bladder cancer 29 . In a study of ovarian cancer, it was found that exosomes from ovarian cancer cells affected fibroblast cells of tumor origin and cells adjacent to the tumor 30 .…”
Section: Effect Of Cdes On Cafsmentioning
confidence: 90%